Measuring HIV stigma for PLHAs and nurses over time in five African countries - William L Holzemer; Lucy N Makoae; Minrie Greeff; Priscilla S Dlamini; Thecla W Kohi; Maureen L Chirwa; Joanne R Naidoo; Kevin Durrheim; Yvette Cuca; Leana R Uys (Taylor & Francis Group, 2009)
The aim of this article is to document the levels of HIV stigma reported by persons living with HIV infections and nurses in Lesotho, Malawi, South Africa, Swaziland and Tanzania over a 1-year period. HIV stigma has been shown to negatively affect the quality of life for people living with HIV infection, their adherence to medication, and their access to care. Few studies have documented HIV stigma by association as experienced by nurses or other health care workers who care for people living with HIV infection. This study used standardised scales to measure the level of HIV stigma over time. A repeated measures cohort design was used to follow persons living with HIV infection and nurses involved in their care from five countries over a 1-year period in a three-wave longitudinal design. The average age of people living with HIV/AIDS (PLHAs) (N=948) was 36.15 years (SD=8.69), and 67.1% (N=617) were female. The average age of nurses (N=887) was 38.44 years (SD=9.63), and 88.6% (N=784) were females. Eighty-four per cent of all PLHAs reported one or more HIV-stigma events at baseline. This declined, but was still significant 1 year later, when 64.9% reported experiencing at least one HIV-stigma event. At baseline, 80.3% of the nurses reported experiencing one or more HIV-stigma events and this increased to 83.7% 1 year later. The study documented high levels of HIV stigma as reported by both PLHAs and nurses in all five of these African countries. These results have implications for stigma reduction interventions, particularly focused at health care providers who experience HIV stigma by association.